PEREMPUAN DAN RASIONALITAS PENAFSIRAN: Studi Terhadap Penafsiran ‘Aisyah RA. - Nafriandi Nafriandi (Kafa`ah: Journal of Gender Studies, 2015)
This study tries to see a pattern of interpretation 'Aisha in the context of woman and the extent of rationalization does in interpreting the verses of the Koran. On its interpretation of the text, 'Aisha was always a functioning reason for researching, analyzing, and to find all the possibilities that exist with the ability to translate it to linking values related text and the same pattern. Then she tried to formulate her thoughts in the form of values and norms with intellectual ability and ijtihad. In the context of woman, 'Aisha was critical that women not only accept what was said by another friend, and a friend who is a friend of the criticism he has recognized capabilities in transmission. 'Aisha is also included in the list of women who are actively involved in teaching the interpretation of early Islam and he is able to coexist with the Prophet's companions were male. This is evidenced by his transmission totaling 5.965 hadith. The phenomenon of 'Aisha was something unique because she was woman, but more rational than the male friend to another and thought he jumped even further by refusing to understand clause textually.